Community-based forest management promotes survival-led livelihood diversification among forest-fringe communities in Uganda - Mawa, Christopher; Tumusiime, David Mwesigye; Babweteera, Fred; Okwir, Eric; Tabuti, John Robert Stephen (Frontiers in Forests and Global Change, 2023)
Livelihood diversification is a prominent feature of rural households in developing countries. It is a strategy commonly pursued by households to enhance their resilience to shocks and/or risks that affect their livelihood. While a common characteristic of Uganda’s community-based forest management (CBFM) is the promotion of alternative livelihood activities to reduce household reliance on natural forest resources from gazetted forests, it is unclear how livelihood diversification has been embraced by households engaged in CBFM. We explore livelihood diversification using cross-sectional survey data collected from 423 households in villages adjacent to Collaborative Forest Management (CFM) compartments and non-CFM compartments of Budongo Central Forest Reserve as well as two Community Forests (CF) in mid-western Uganda. We quantified the levels of diversification and fitted a Gini-Simpson Diversity Index as the response variable in two Tobit regression models to examine the determinants of livelihood diversification among forest-fringe communities in CFM and CF sites. Our results reveal high levels of survival-led household livelihood diversification in the area, with an average household engaging in five livelihood activities that were predominantly on-farm or involved the extraction of forest products for subsistence. In the CFM sites, livelihood diversification levels significantly increased with household heads’ duration of residence in the village and membership in other social groups in the village. In villages adjacent to the community forests, only the household dependency ratio positively influenced household livelihood diversification. Membership in forest conservation groups did not significantly predict the level of household livelihood diversification. Given the current survival-led diversification that these communities pursue, we recommended that development and conservation agencies in the area and other similar sites of CBFM deliberately enhance household access to high-return on-farm and non-farm livelihood activities to achieve meaningful transformations in rural livelihoods.